2007
DOI: 10.2214/ajr.05.1950
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mammographic Parenchymal Pattern in Screening-Detected and Interval Invasive Breast Cancers on Pathologic Features, Mammographic Features, and Patient Survival

Abstract: The prognosis of screened women presenting with breast cancer is unrelated to dense mammographic parenchymal pattern despite an excess of interval cancers and larger screening-detected tumors in this group. These data support the mammographic screening of women with dense parenchymal patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 30 publications
9
64
5
Order By: Relevance
“…Similar results were found among screening-detected, invasive, and small tumors. Our results are in line with Porter et al who reported a higher proportion of spiculated masses among women with fat involuted breasts, as well as a higher proportion of architectural distortions among women with dense breasts (18).…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were found among screening-detected, invasive, and small tumors. Our results are in line with Porter et al who reported a higher proportion of spiculated masses among women with fat involuted breasts, as well as a higher proportion of architectural distortions among women with dense breasts (18).…”
Section: Discussionsupporting
confidence: 93%
“…Including only deaths from BC gave a case fatality rate ratio of 0.53 ). An earlier study indicated a slightly worse BC-specific survival for BI-RADS category 2 cancers than for category 1, 3, and 4 cancers (Porter et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Only a few studies have examined mammographic density in relation to breast tumor characteristics, and most of these studies assessed mammographic density of the contralateral breast at the time of cancer diagnosis (7)(8)(9)(10). These illustrated positive associations between mammographic density and tumor size, lymphatic invasion, later stage, and lymph node status but were inconsistent on associations with tumor grade and estrogen receptor status of the tumor.…”
Section: Introductionmentioning
confidence: 99%